Ground Walk Training Versus Treadmill Training on Endurance Capacity and Quality of Life in COPD Patients - Saranya, Yayathirajan; Manoj Abraham, Manoharlal; Mahesh, Ramraja; Vinosh Kumar, Purushothaman; Hii, Everlynn, Y.X. (INTI International University, 2023)
Background: Pulmonary rehabilitation is mainly fascinated by equipment-dependent training such as treadmill and cycle training. But not all patients are affordable due to its high cost of pay for the entire treatment course which may vary from six to twelve weeks. Ground walk training is the simplicity of performance, and it is easy to monitor the exercise training program. Though, ground walk training is very feasible and easily accessible by the patients, it is still not beenpracticed widely as alternative to the treadmill training in pulmonary rehabilitation. Hence, this study was aimed to compare the effectiveness of ground walk training and treadmill training on improving the endurance capacity and quality of life in COPD patients. Methods: A quasiexperimental study was conducted and a total of 30 COPD patients were recruited. Participants with age group between 45-60 years, both gender, stage II to IV (GOLD) and reduced exercise tolerance (Modified Borg Scale – Score > 3) were included into this study. Participants were divided into two groups with 15 in each group (group A and group B). Group A received ground walktraining and group B received treadmill training for a period of 6 weeks, 3days/week, 30-45mins/session. The outcome measures including endurance capacity and quality oflife was assessed using six-minute walk test and chronic respiratory diseasequestionnaire. Results: Independent sample ‘t’ test was used to compare the outcome among group A and B. There was a significant increase in endurance capacity with p≤0.001 in group A (326.40±3.05) compared to group B (310.80±3.31) with ‘t’ value (9.09). Quality of life showed significantly increased ingroup A (5.77±0.53) compared to group B (5.23±0.66) with ‘t’ value (3.33) and p≤0.001. Conclusion: Ground walk training showed significant improvement on endurance capacity and quality of life in COPD patients compared to treadmill training.